Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 2 - Limits - 2.3 Basic Limit Laws - Exercises - Page 59: 30


$=\dfrac {-2}{3}$

Work Step by Step

$\lim _{x\rightarrow -4}\dfrac {f\left( x\right) +1}{3g\left( x\right) -9}=\dfrac {\lim _{x\rightarrow -4}f\left( x\right) +1}{3\lim _{x\rightarrow -4}g\left( x\right) -9}=\dfrac {3+1}{3\times 1-9}=\dfrac {4}{-6}=\dfrac {-2}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.